PENERAPAN MODEL KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS III SD NEGERI 3 TELUK RHU - Junaidi Junaidi; Zariul Antosa; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak: This research is a classroom study that is motivated by the low learning outcomes of the students PKN whose average class is still at 72.64, while the completion standard that is in grade IV SD Negeri 3 Rhu Bay is 70. Of the 25 students only 12 people are completed while 13 others have not been completed. This study was conducted in two cycles, carried out in even semester 2016/2017. This study aims to improve the learning outcomes of third grade students of SD Negeri 3 Teluk Rhu by applying Team Assisted Individualization (TAI) learning approach. The TAI learning approach is a learning model that encourages students to discover the concepts of learning by working in groups. The instrument of this study consists of. The study was conducted from March 2016 to May 2017. Research data were analyzed using MS.Excel including teacher activity data and student activity and student learning result data. Data analysis of teacher activity and student activity on observation result done by observer during action implementation. Results of data analysis of student learning outcomes performed after the implementation of daily repetition cycle I and cycle II. Based on the results of the observer observation of teacher activity and student activity always increases in each cycle. In the first cycle only reached 54.17%, in the second cycle increased to 83.33% while in the student activity on the first cycle only 41.67%, in the second cycle increased to 87.50%. Student learning outcomes also experienced an increase as follows, the basic skoe was 72.64 which then increased in cycle II to 79.60 with an increase of 9.58%. Completeness of student learning outcomes on a basic score of only 12 people, in cycle II all students complete. This shows that cooperative learning type TAI can improve the learning outcomes of third grade students of SD Negeri 3 Teluk Rhu.Keywords: Cooperative type TAI, PKN Learning Outcomes